Śiva-pratāpa - Tivārī, Du. Ā. (Durgāprasāda Āsārāma), 1887-1939 (SAMP early 20th-century Indian books project, 1928)
Poetic work on life of Raja Shivaji, 1627-1680, based on Śivabāvanī by Bhūshaṇa, 1613?-1715?